Solitude as an act of hedonism in Bryce Andrews’ Badluck Way - Mohd Zaimin Haris Fathillah; Ravichandran Vengadasamy (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper argues that the author’s preference for solitude in Bryce Andrew’s Badluck Way is essentially hedonistic in nature. Solitude constitutes human existence and experience. The concept of ‘pain and pleasure’ predicates hedonism. The intersectionality between experiential solitude and hedonism is unfortunately inconceivable despite a plethora of discourse including literature. In numerous literary texts, solitude has been the pivotal entry point to ascertain and expound both fictional and nonfictional characters’ actions and behaviours. The same can be said about hedonism. However, there is little to no literary studies conducted to explore the common linkage between solitude and hedonistic views. Fred Feldman’s (2004) Attitudinal Hedonism theory and his six Intrinsic Attitudinal Pleasure features underpinned the study. Findings disclosed that many pleasure taking aspects in solitude are inherently hedonistic. Selected excerpts revealed that hedonism and pleasure taking played a predominant role in asserting the author’s predilection for solitariness. This paper responds to the need for investigation of the singularisation of solitude-hedonism concept as a means of heightening interdisciplinary awareness and enabling inter-discourse studies of literary and philosophical scholarship alike.